Propuesta de un plan de minimización de los residuos sólidos de la facultad de ecología provincia de Moyobamba - Mestanza Solano, Willy (2011)
The formless qualified present.· " O.ffer of a Plan of Minimization of the Sol id Residues of the Faculty ofEcology- Moyobamba's Province "it considers as general aim to reduce the quantity in volume and dangerousness of the solid residues of the Faculty of Ecology of San's Martín National University-T, applying methods and 1 or technologies of minimization, which is applicable to the current reality by means of the specific aims, to realize the diagnosis ofthe current situation ofthe solid residues ofthe Faculty ofEcology, to identify the generating sources of solid organic and inorganic residues in the Faculty of Ecology, propose and describe techniques and 1 or methods for minimizing solid waste to reduce the generation and encourage their reuse. The methodology used in the present monographic work, consists of 03 stages, which are described later. Cabinet Stage lnitial: it consists of the summary and selection of the information of the different bibliographical, manual sources, technical guides, applied experiences and web pages related to the topic. Field stage: it consists of the accomplishment of the diagnosis of the faculty of Ecology as institution, and situational diagnosis of the so lid residues, carrying out the characterization to determine the GPC and the physical composition. Cabinet Final Stage: lt consists of the processing and analysis of the summary of information obtained of the bibliographical information and the field stage, with the purpose of elaborating the Plan of Minimization of the solid residues of the Faculty of Ecology proposing technologies and methods for the minimization ofthe solid residues. The obtained results show the nonexistence of a plan of managing, inadequate storage of the residues inside the Faculty. Of the characterization there was obtained that the GPC of the Faculty is 0.034 Kg/est/día and the physical composition is composed by 65.4 % of organic reusable residues for the production of compost and humus, 23.13 % is also reusable (recyclable) and 11.47 % is not reusable residues, there being needed for these residues a total of 05 containers by capacity of 53 lt/cu. whose volume is of 0.076 m3. Finally inside the Plan of Minimization they propose technologies and methods of minimization of solid residues for the faculty, with which there would be obtained big economic, social and environmental benefits.